Harvest of the Oleaginous Microalgae Scenedesmus obtusiusculus by Flocculation From Culture Based on Natural Water Sources - Bracharz, Felix; Helmdach, Daniel; Aschenbrenner, Isabel; Funck, Nils; Wibberg, Daniel; Winkler, Anika; Bohnen, Frank; Kalinowski, Jörn; Mehlmer, Norbert; Brück, Thomas B. (Frontiers in Bioengineering and Biotechnology, 2018)
Harvest and dewatering contributes a significant economical burden for industrial algae biomass production. To mitigate these effects energy efficient techniques for these process steps have to be developed. Flocculation of the microalgae Scenedesmus obtusiusculus in salt based medium was induced by pH-shift and alternatively by addition of two biological flocculants, chitosan and the commercial tannin CFL-PT. This is the first time that CFL-PT is used as an algae flocculant particularly focusing on harvesting of halophilic strains.The method was characterized and subsequently optimized. In comparison to biological flocculants, induction by pH shift is far cheaper, but due to buffering effects of the brackish cultivation medium infeasible amounts of base are required to raise the pH. Tannin appears to be superior compared to chitosan not only in the absence of algae organic matter (AOM), but tannin-based harvest is also more robust regarding culture pH in presence of AOM. A higher flocculant-demand for modified tannin compared to chitosan is offset by the lower price. Given the employed strain and cultivation conditions, cultivation time had no pronounced effect on flocculation efficiencies (FE) while algae zeta-potential and bacterial communities also remained stable.